2020
DOI: 10.1109/access.2020.3006040
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Data Dissemination Protocols for Connected Autonomous Vehicles

Abstract: An overwhelmed number of vehicles have wrecked the current system of transportation due to rapid growth in population. Smart cities are the novel innovation that is inevitable to curb the problems of traffic jams, unorganized traffic, environmental pollution, and slow response rate to emergency situations. The intelligent transportation system (ITS) is an integral part of smart cities allowing communications and interaction among vehicles. An autonomous vehicle is the key element of ITS and the mass implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…In contrast, the GPSR and GPCR confirmed to be more efficient in the event of overhead and latency. Paper [10] presented the performance investigation for diverse environments (Real-world, Highway Scenario, and Manhattan Grid) by density variation of vehicles for three protocols (AODV, DSR, and DSDV). It observed that the DSR performance, in general, is efficient in both terms of throughput and latency, as compared to AODV and DSDV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, the GPSR and GPCR confirmed to be more efficient in the event of overhead and latency. Paper [10] presented the performance investigation for diverse environments (Real-world, Highway Scenario, and Manhattan Grid) by density variation of vehicles for three protocols (AODV, DSR, and DSDV). It observed that the DSR performance, in general, is efficient in both terms of throughput and latency, as compared to AODV and DSDV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [19], different routing protocols that can be used for communications among autonomous vehicles have been investigated. In [20], a routing scheme in a drones-connected vehicle's network is proposed to reduce communication delay in a crowded environment.…”
Section: Related Workmentioning
confidence: 99%
“…A SERIOUS concentration has been made in the vehicular ad hoc network (VANET) technology [1], [2] since 1990s, and especially in the last decade, many advancements have been seen. Internet of Things (IoT) has been deployed (and being deployed) in various domains, such as agriculture [3], [4], healthcare [5]- [8], cloud computing [9], [10], edge computing [11], smart cities [12]- [14], smart homes [15], etc [16], [17].…”
Section: Introductionmentioning
confidence: 99%